Evaluation of Airway Measurements in Class II Patients Following Functional Treatment - Merve Göymen; Dler Mourad; Ayşegül Güleç (Galenos Yayinevi, 2019)
Objective:This study aimed to evaluate the effect of fixed and removable functional treatment on pharyngeal airway measurements in class II patients.Methods:In this study, patients treated with fixed (Forsus Fatigue Resistant Device-FRD) and removable (twin-block-TWB) appliances were included (n=15, eight females, seven males in each group). These groups were compared with untreated individuals as the control group (n=10). The mean age of individuals was 13.22±2.39 years. Initial and post-treatment cephalometric radiographs were digitized, and the sagittal pharyngeal airway changes were evaluated. The pharyngeal airway was divided into the nasopharynx, oropharynx, and hypopharynx. The one-way ANOVA, Kruskal-Wallis test, and paired samples t-test were used for statistical analyses.Results:At the initial values, no statistically significant difference was observed between the groups. Only the ANB values differed between the groups (p<0.05). Although the skeletal effects of removable and fixed treatment were not exactly the same, the changes of the airway dimensions were similar.Conclusion:The TWB and FRD appliances lead to an increase in nasopharynx, oropharynx, and hypopharynx sagittal dimensions. However, in terms of the effect on airway sagittal dimensions, there was no significant difference between treatment groups and the control group.